Novel inhibitors and activity-based probes targeting serine proteases - Timothy E. G. Ferguson; James A. Reihill; S. Lorraine Martin; Brian Walker (Frontiers in Chemistry, 2022)
Serine proteases play varied and manifold roles in important biological, physiological, and pathological processes. These include viral, bacterial, and parasitic infection, allergic sensitization, tumor invasion, and metastasis. The use of activity-based profiling has been foundational in pinpointing the precise roles of serine proteases across this myriad of processes. A broad range of serine protease-targeted activity-based probe (ABP) chemotypes have been developed and we have recently introduced biotinylated and “clickable” peptides containing P1 N-alkyl glycine arginine N-hydroxy succinimidyl (NHS) carbamates as ABPs for detection/profiling of trypsin-like serine proteases. This present study provides synthetic details for the preparation of additional examples of this ABP chemotype, which function as potent irreversible inhibitors of their respective target serine protease. We describe their use for the activity-based profiling of a broad range of serine proteases including trypsin, the trypsin-like protease plasmin, chymotrypsin, cathepsin G, and neutrophil elastase (NE), including the profiling of the latter protease in clinical samples obtained from patients with cystic fibrosis.